(untitled) (Nóema, 2016)
The essay is about the idea of an education based on the principles of the socratic and enlightenment tradition. This idea should also provide the horizon of understanding and the practical rule for the specialized knowledge. The sharing of this idea calls to action against the authoritarian and privatistic trends of our times. Teachers in particular, who recognize themselves in the values of public, secular and constitutional school, are called to this effort of resistance.